Illegality, inc.: clandestine migration and the business of bordering Europe - Andersson, Ruben (California series in public anthropology, 2014)
"In this groundbreaking ethnography, Ruben Andersson, a gifted journalist and anthropologist, travels with a group of African migrants from Senegal and Mali to the Spanish North African enclaves of Ceuta and Melilla. Through the voices of his informants themselves, Anderson explores, viscerally and emphatically, how migration meets and interacts with its target--the clandestine migrant. This vivid, rich work examines the subterranean migration flow from Africa to Europe, and shifts the focus from the concept of "illegal immigrants" to an exploration of suffering and resilience. This fascinating and accessible book is a must-read for anyone interested in the politics of international migration and the changing texture of global culture"--